THE PROBLEM OF ENERGY EFFICIENCY OF THE GEOTHERMAL CIRCULATION SYSTEM IN DIFFERENT MODES OF REINJECTION OF THE COOLANT - D. K. Djavatov; A. A. Azizov (Юг России: экология, развитие)
Aim. Advanced technologies are crucial for widespread use of geothermal energy to ensure its competitiveness with conventional forms of energy. To date, the basis for the development of geothermal energy is the technology of extracting the heat transfer fluids from the subsoil. There are the following ways to extract the coolant: freeflow; pumping and circular methods. Of greatest interest is the technology to harness the geothermal energy based on geothermal circulatory system (GCS). There is the problem of the right choice of technological parameters for geothermal systems to ensure their effective functioning.Methods. We consider the development of geothermal energy technology based on geothermal circulatory system, as this technology solves the dumping of the waste water containing environmentally harmful substances. In addition to the environmental issues, this technology makes it possible to intensify the process of production and the degree of extraction of thermal resources, which significantly increases the potential for geothermal heat resources in terms of the fuel and energy balance.Findings. Were carried out optimization calculations for Ternairsky deposits of thermal waters. In the calculations, was taken into account the temperature dependence of important characteristics, such as the density and heat capacity of the coolant.Conclusions. There is the critical temperature of the coolant injected, depending on the flow rate and the diameter of the well, ensuring the effective functioning of the geothermal circulatory systems.